2015
DOI: 10.1021/nn5072254
|View full text |Cite
|
Sign up to set email alerts
|

Gallium Plasmonics: Deep Subwavelength Spectroscopic Imaging of Single and Interacting Gallium Nanoparticles

Abstract: Gallium has recently been demonstrated as a phasechange plasmonic material offering UV tunability, facile synthesis, and a remarkable stability due to its thin, self-terminating native oxide. However, the dense irregular nanoparticle (NP) ensembles fabricated by molecular-beam epitaxy make optical measurements of individual particles challenging. Here we employ hyperspectral cathodoluminescence (CL) microscopy to characterize the response of single Ga NPs of various sizes within an irregular ensemble by spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
136
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(152 citation statements)
references
References 68 publications
(170 reference statements)
16
136
0
Order By: Relevance
“…Similar results were obtained by Albella et al [60] through a numerical study based on the Discrete Dipole Approximation (DDA) [61]. Other methods used to study this type of nanoparticles include variable-angle spectroscopic and Mueller matrix ellipsometry [62] or hyperspectral cathodoluminescence imaging [63].…”
Section: Galliumsupporting
confidence: 72%
“…Similar results were obtained by Albella et al [60] through a numerical study based on the Discrete Dipole Approximation (DDA) [61]. Other methods used to study this type of nanoparticles include variable-angle spectroscopic and Mueller matrix ellipsometry [62] or hyperspectral cathodoluminescence imaging [63].…”
Section: Galliumsupporting
confidence: 72%
“…1a), we observe that the NP contact angle on the substrate plane is close to 90º, giving rise to hemispherical shapes. This morphology results from the surface tension of liquid Ga on the silicon substrate, and it is preserved during the functionalization works due to the formation of a thin oxide film on the NP surface (Knight et al 2015;Wu et al 2009). …”
Section: Nanoparticle Characterizationmentioning
confidence: 99%
“…While the formation of Ga grains from thinly deposited Ga films may be explained through Ostwald ripening [31] and references within, the formation of Ga grains on films whose thickness is much larger than the actual height of the grains is not trivial. Our STM measurements revealed that the first deposited Ga film had an approximate thickness of 32 µm and its surface is densely populated with grains that have large aspect ratio values from 1-1.8.…”
Section: Discussionmentioning
confidence: 99%
“…The Ga deposition method resembles the procedure used by Knight et al; [31] the main difference involved a longer deposition time, which resulted in the larger thicknesses of our Ga films. The films were prepared by depositing Ga (99.99% purity, Gallium Source, USA) on p type (boron doped) Si(111) mono-wafer substrates (Institute of Electronic Materials Technology, Poland).…”
Section: Deposition Of Galliummentioning
confidence: 99%
See 1 more Smart Citation